Pengembangan Alat Monitoring Kanopi Pada Sistem Smart Home Berbasis IoT (Internet of Things) - Bagus Adi Nugroho; Rudi Susanto; Afu Ichsan Pradana (Universitas Islam Raden Rahmat, Malang, 2024)
The main problem if using a regular canopy, if the room is used for activities such as drying clothes, sunlight cannot enter the area and the canopy becomes less effective in terms of design or benefits. This research aims to develop a tool to monitor and control the canopy automatically using the prototyping method starting from Communication, Quick Plan, Modeling Quick Design, Construction of Prototype, and Deployment Delivery & Feedback. This research produces innovative solutions to increase the effectiveness of canopies, especially if they are on limited land, using microcontrollers combined with Raindrop, DHT22, BH1750 sensors. The addition of the DHT22 humidity sensor and the BH1750 light sensor can help the Raindrop sensor in validating rainy or sunny conditions, making the system more accurate. The test results of the three sensors based on the rules / regulations obtained a system that can carry out the task as expected. Based on Black Box testing on the IoT System, the results show that the system can be integrated with the Blynk platform properly.